The parameter bayesian estimation of two-parameter exponential-poisson distribution and its optimal property. Issue 4 (3rd July 2016) - Xu, Biao; Guo, Yan; Zhu, Ning
Abstract: Based on the general non-information prior distribution, we study the Bayes estimations of the parameter of the Exponential-Poisson Distribution under some symmetrical and unsymmetrical loss functions. As parameter b is fixed, the Bayesian estimations of another parameter l are given. Simulation studies are performed to access the accuracy of the different estimations. The simulation result illustrates different random sample size could select different loss functions, then, it is improved the precision of unknown parameters under the loss functions.